MCAST: Mobility-aware Channel-Availability based Channel Selection Technique - Rahman, Md. Arafatur; Savoia, Roberto; Uddin, Mohammad Moshee (2015)
A key issue in cognitive radio networks is the design of a channel selection technique that guarantees to utilize the highest available channel in presence of the dynamic activity of primary users. Usually, the channel selection techniques that operate in this kind of network are based on the channelavailability probability. In the static primary user’s scenario, this probability can be a priori known or simply estimated from the channel occupancy history. However, in the mobile primary user’s scenario, this probability dynamically varies in time due to the changes of the primary user’s position. In order to exploit the dynamic variation of the channel availability, in this paper we design a novel Mobility-aware Channel-Availability based channel Selection Technique (MCAST) that ensures to select the channel with the highest channel availability probability in a given temporal interval. The simulation results highlight the benefits of the proposed technique in presence of primary user’s mobility. Moreover, we evaluate the effectiveness of MCAST in a scenario of practical interest by adopting this technique in a recently proposed routing metric designed for this network.